SUN-LB025 Superior Mesenteric Artery Thrombosis: An Uncommon Complication of Diabetic Ketoacidosis - Saini, Khushpreet Kaur (J Endocr Soc, 2019)
Introduction: Diabetic Ketoacidosis (DKA) has been shown to promote a prothrombotic state. Mortality rate in DKA can be as high as 20% due to thromboembolic complications. Acute mesenteric ischemia has mortality rates of 60-80% due to late and difficult diagnosis. Very few cases of superior mesenteric artery (SMA) thrombosis associated with DKA have been described in literature. The presentation of acute SMA thrombosis can be masked by concurrent DKA due to its non-specific signs and symptoms and laboratory markers leading to delay in diagnosis and treatment. Case: A 68-year-old female with Type 2 diabetes since 25 years was hospitalized with nausea, vomiting and abdominal pain of 3 days duration. Initial lab work showed: Serum glucose 631 mg/dl (n 70-140 mg/dl), bicarbonate 11 mmol/L (n 22-28 mmol/L), anion gap 32(n 12-16), lactic acid 3.0 mmol/L (n 0.5-2.2 mmol/L), HbA1c 14.1 % (n 4.6-6.5%) and serum osmolarity of 310 mOsm/kg (n 275-295 mOsm/kg). CECT abdomen on admission was unremarkable. She was adequately managed for DKA with intravenous fluids and insulin. Lactic acid normalized with fluids and anion-gap closed within 24 hours of admission. However, she kept complaining of diffuse abdominal pain described as sharp and deep inside the abdomen. D-dimer and repeat lactic acid were elevated at 1,155 ng/ml (n 150-234 ng/ml) and 2.4 mmol/L (n 0.5-2.2 mmol/L) respectively. CT angiography obtained at 48 hours from the time of admission showed occlusion of SMA at its mid-portion, approximately 7 cm distally from origin with abrupt loss of contrast signal at branch point of the ileocolic artery after several jejunal branches. She underwent urgent SMA thrombectomy, exploratory laparotomy and small bowel resection. Echocardiogram didn’t reveal any cardiac source of embolism or septal defects. EKG showed sinus rhythm and patient didn't have any prior history of thromboembolism or cardiac arrhythmias. Laboratory panel for thrombophilia and screening for auto-immune disorders was negative. Patient recovered well post surgery and was started on anti-coagulation. Discussion: We didn't find any other risk factor for arterial thrombosis in our case other than diabetic ketoacidosis and uncontrolled diabetes. Studies have shown that Free Protein S and Protein C activity levels decrease and von Willebrand factor levels increase during DKA. Platelet hyperreactivity, coagulation activation, hyperosmolarity, endothelial damage and impaired fibrinolysis- all contribute to hypercoagulability during DKA. Routine use of prophylactic anticoagulation in DKA is controversial. Clinicians should maintain a high index of suspicion of thrombosis in DKA. Pain out of proportion to the physical exam findings and persistent abdominal pain and lactic acidosis despite treatment should point towards mesenteric ischemia. Early diagnosis and treatment of mesenteric ischemia in critical in influencing the survival. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.